PENGARUH PELAYANAN PERPUSTAKAAN TERHADAP KEPUASAN PEMUSTAKA DI PERPUSTAKAAN FAKULTAS ADAB DAN HUMANIORA UIN RADEN FATAH PALEMBANG - Kris Setyaningsih (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2016)
The study evaluated the effect of library services to the satisfaction of library visitors in culture and humanities faculty uin Raden Fatah Palembang, motivated by the limitations of the materials needed by pemustaka. This type of research is a kind of quantitative research. Data analysis used the